Pembelajaran Bahasa Inggris Berbasis Permainan untuk Anak Usia Dini: Studi Literatur - Muhammad Rizky Rochmawan (Sentra Cendekia, 2023)
This study analyzes and presents a literature study on the use of games as an approach to learning English at the elementary education level. The method used is a literature study by collecting data from various reliable sources. The focus of the research is the use of games in learning English in the early stages of children's education. The results of the study show that game-based learning English has significant potential in increasing student motivation and engagement, facilitating social interaction, and expanding understanding of English vocabulary and grammar. The use of games can also stimulate children's cognitive abilities and creativity and enrich their learning experience. However, the research also identified several challenges associated with the use of games in learning English, such as the need to design games that fit the curriculum, provide access to the necessary technological tools, and balance the use of games with other learning activities. This study contributes to an understanding of the use of games in learning English at the elementary education level. These findings can assist educators and curriculum developers in designing innovative and engaging learning strategies, which can enrich children's English learning experiences.